1990
DOI: 10.1021/ic00342a033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of monosubstituted borane adducts of diethyl [(dimethylamino)methyl]phosphonate

Abstract: The cyanoborane adduct of diethyl ((dimethylamino)methyl)phosphonate, (Et0)2P(0)CH2NMe2-BH2CN (1), was N-alkylated with Et3OBF4 to give the nitrilium salt (Et0)2P(0)CH2NMe2-BH2CNEtBF4 (2). Hydrolysis of 2 with water gave the corresponding carboxyborane (Et0)2P(0)CH2NMe2-BH2C02H (3), and with alkali gave the carbamoyl derivative (Et0)2P(0)-CH2NMe2-BH2CONHEt (4). Reaction of the carbamoyl compound 4 with Et3OBF4 followed by base treatment resulted in the formation of an imino ether, (Et0)2P(0)CH2NMe2-BH2C(0Et)=N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The synthesis of 5 was attempted by acidic hydrolysis of the known [amine-bis( C -methoxy- N -ethylimidate)hydroboron(2+)] cations ( 6 ): 29 These experiments were based on literature data stating that hydrolyses of C -alkoxy- N -alkylimidates in acidic media typically result in the formation of carboxylic acid esters and some amine-alkoxycarbonylboranes are known to be synthesized from [amine-( N -ethylnitrilium)dihydroboron(1+)] cations via amine-( C -alkoxy- N -ethylimidate)dihydroboron(1+)] species. , Therefore, the hydrolyses of 6a,b,f , which were readily obtained by nucleophilic addition of methanol to 1a,b,f , were systematically studied (basically by 1 H NMR monitoring) at various pH values. Our findings, different from those expected, can be summarized in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 5 was attempted by acidic hydrolysis of the known [amine-bis( C -methoxy- N -ethylimidate)hydroboron(2+)] cations ( 6 ): 29 These experiments were based on literature data stating that hydrolyses of C -alkoxy- N -alkylimidates in acidic media typically result in the formation of carboxylic acid esters and some amine-alkoxycarbonylboranes are known to be synthesized from [amine-( N -ethylnitrilium)dihydroboron(1+)] cations via amine-( C -alkoxy- N -ethylimidate)dihydroboron(1+)] species. , Therefore, the hydrolyses of 6a,b,f , which were readily obtained by nucleophilic addition of methanol to 1a,b,f , were systematically studied (basically by 1 H NMR monitoring) at various pH values. Our findings, different from those expected, can be summarized in Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous papers in the literature describe the ethylation reactions (Scheme , ii) employing 50−100% excess of Et 3 OBF 4 and 24−72 h reaction times. ,, In contrast, we have found that diamine-bis(cyanoboranes) 1 could be completely converted into their bis(ethylnitrilium dihydroborane) tetrafluoroborates 2 in 2−3 h using a small (3−5%) excess of Et 3 OBF 4 .…”
Section: Resultsmentioning
confidence: 99%